Analysis of Nuclear Security and Safety Integration Using Survey Responses and Pairwise Comparison Methods - Sheila V Gbormittah; Theodore A Thomas; Jason Timothy Harris (International Journal of Nuclear Security, 2025)
Integrating nuclear security and safety is important for implementing and sustaining nuclear technology because it promises improved and effective management. This integration is an ongoing effort to ensure that both work together with minimal conflicts. This research aimed to determine the preferred level at which nuclear security and nuclear safety integrate by using the pairwise comparison methods of decision-making. This methodology used survey responses from women nuclear professionals to identify the most-desired criteria at three levels: strategic, operational, and cultural. The strategic level includes actions that government officials and regulators can take. The operational level encompasses actions that deliver the integration. The cultural level involves actions that must be taken to change an organization’s attitude toward integration. The survey results indicated that a majority (75%) of respondents agree nuclear security and safety integrate when the organizational structure and legal framework support integration at the strategic level. A majority (75%) of respondents agreed that nuclear security integrates with nuclear safety when the organizational structure and the legal framework support integration at the strategic level. A majority (70%) of respondents agreed that work comprising support for implementing an integrated interface and reporting mechanisms to report and address nuclear security and safety conflicts facilitates integration at the operational level. At the cultural level, more than half (55%) of respondents agreed that nuclear security and nuclear safety integration occurs when leadership is supportive and clearly accountable and staff fully understand their roles and responsibilities. Applying pairwise comparison methods to the survey data, nuclear security integrates with nuclear safety most at the operational level (with a priority of 0.44). The strategic level rated as the second highest priority (0.37), and the cultural level had the lowest priority (0.19). The results show that integrating nuclear security and safety is most recommended at the operational level. The sensitivity analysis (both sum rank and equal weights) showed that the best alternative for integrating nuclear safety and security is at the strategic level.
Keywords: nuclear security; nuclear safety; surveys; pairwise comparisons; integration